THE EFFECT OF FAMILY HARMONY ON STUDENT MORAL BEHAVIOR AT SMA KRISTEN TOMOHON - Novi Syahrudin; Meisie L. Mangantes; Ariantje J.A. Sundah (Prodi Bimbingan Konseling Universitas Negeri Manado, 2022)
This study aims to determine the effect of family harmony on the moral behavior of students at SMA Kristen 1 Tomohon for the academic year 2020/2021. This research was conducted using a quantitative research approach with a correlation method, the population of this study was 788 students with a sample of 79 students at SMA Kristen 1 Tomohon and the sampling process was taken by simple random sampling. Data was collected by distributing questionnaires with a Likert scale, and data were analyzed using simple linear regression analysis techniques with the help of a computer program SPSS 23 for windows. The results of this study indicate that there is an effect of family harmony on students' moral behavior with the regression equation Y = 40.685 + 0.668 X, with the ratio of the increase in the two variables quantitatively is 1: 0.668 this comparison shows that if there is an increase of one time / unit in the harmony variable family (X), there will be an increase of 0.668 in the moral behavior variable (Y). The regression equation is significant or will not be tested using the Fcount value at the significant level of 0.05, and it is obtained that the Fcount is 75.035 with a significant value of 0.000 <0.005, then Ha is accepted. The conclusion is that the Ha hypothesis which says there is an effect of family harmony on the moral behavior of students at SMA Kristen 1 Tomohon is accepted and significant, this is indicated by the value of the regression coefficient (F) of 75.035 with a significant of 0.000